Evaluación y Plan de Control de la Contaminación Sonora en Conductores de Mototaxis en la Ciudad de Moyobamba - Rosas Llerena, Eduardo (2004)
The goal of this thesis is to help to resolve the sonorous pollution produced by mototaxi in the city of Moyobamba, through appropriate actions. To obtain this goal it has appraised the urban sonorous pollution in areas of more mototaxi traffic. It has made a preliminary research about the consequences of that pollution on the mototaxi driver's auditory sense, since this people are more exposed to urban noise. In order to distinguish the effect of noise on the mototaxi driver's auditory sense, it has made, to parallel, a preliminary research on no mototaxi driver people. The end the report shows a plan to control the sonorous pollution, which it may be a environmental management instrument for the city government of Moyobamba. The initial hypothesis has been: "the sonorous pressure level produced by mototaxi exceed nearly 35 decibel on permissible exposure limit and cause permanent increase of mototaxi driver's auditory threshold on 4 decibel to 1000 Hz, to exposure period nearly 5 years, in the city of Moyobamba" Nevertheless, at the beginning of research, that hypothesis change to: (1) ''the sonorous pressure level at the city of Moyobamba cause in the main the mototaxi traffic is bigger national environmental quality standard for noise", (2) "the noise produced by mototaxi is bigger the World Health Organization's permissible limit exposure — 8 hours, noises more big may be loss the people's auditory sense" and (3) "exposure to noises for mototaxi drivers, cause them an loss auditory sense bigger to other exposed people no mototaxi drivers". It has evaluate urban noise from 46 points appropriately located in all city, beginning which it has a new perspective in current time urban noise before unknown. It has been used a pocket instrument — sound level meter — to evaluate sonorous pressure level, which is satisfactory for the Reglamento de la Ordenanzal NO 0151985/MLM's conditions. In these conditions, the instrument's purpose is approach to the human hearing's response to sonorous frequency2 on street, to distances no bigger 7 meters. It accepted as no necessary, to distances smaller 100 meters, to consider Reglamento de la Ordenanza NO 01 S — Decreto NO 072-A del 10 de Octubre de 1986 —Articulo 90. 2 Guias para el Ruido Urbano — OMS, 1999 Pig 2. X environmental physical parameters as environmental temperature, relative wet and wind's velocity . It has researched sonorous pressure level on mototaxi 3 States: with motor running but mototaxi stopped, travelling with one passenger, and travelling with two passengers. It was used the same sound level meter which was used for research the urban sonorous pressure level. The auditory tests were carrying out for mototaxi drivers and no mototaxi drivers. These auditory tests were air type. ESSALUD Hospital of Moyobamba has collaborated with technical staff and audiometer. As a results of this thesis it has (I) the city of Moyobamba show a serious sonorous pollution, it show noise levels bigger the national environmental quality standard, (2) these noise levels are caused in the main by mototaxi traffc, which produce noise bigger the national environmental quality standard, and (3) mototaxi drivers show loss of auditory sense bigger no mototaxi driver people. In addition it has as another result the people no mototaxi driver to show loss of auditory sense, probably caused by urban sonorous pollution. And there are neither local norms nor control actions to resolve the urban sonorous pollution or to protect people in this state. Finally this thesis recommends and presents following actions for control and mitigate the urban noise: (I) an Environmental Education Programme to responsible people of sonorous pollution, (2) a Local Law Project about sonorous pollution in the city of Moyobamba, and (3) a guidelines to mitigate urban noise and protect people and urban environmental.